Raid of no return : a World War II tale of the Doolittle Raid - Hale, Nathan, 1976- (2017)
On December 7, 1941, the Japanese bombed Pearl Harbor, officially bringing the United States into World War II. A new generation of pilots were recruited to fly bombing missions for the United States, and from that group, volunteers were requested for a dangerous secret assignment. For the first time in American history, Army bombers would be launched from an aircraft carrier.
Maps on liner papers.
8-12
Keywords: Doolittle, James Harold, -- 1896-1993 -- Juvenile literature; Doolittle, James Harold, -- 1896-1993 -- Comic books, strips, etc; World War, 1939-1945 -- Aerial operations, American -- Juvenile literature; World War, 1939-1945 -- Aerial operations, American -- Comic books, strips, etc; World War, 1939-1945 -- Campaigns -- Japan -- Juvenile literature; World War, 1939-1945 -- Campaigns -- Japan -- Comic books, strips, etc; Tokyo (Japan) -- History -- Bombardment, 1942 -- Juvenile literature; Tokyo (Japan) -- History -- Bombardment, 1942 -- Comic books, strips, etc; Graphic novels; Comic books, strips, etc; Graphic novels; History; Juvenile works